Vitamin D supplementation for COVID-19: is it necessary? - Santosa, Agus (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2020)
The development of the COVID-19 vaccine is currently quite encouraging amid increasing mortality and transmission of the COVID-19 virus in various countries. Apart from vaccination, the government also needs to consider vitamin D supplementation policies because it has a significant role in boosting the immune system.